THE STUDENTS’ ERROR IN USING COHESIVE DEVICES IN ESSAY WRITING (THE DESCRIPTIVE EXPLOTATORY STUDY AT THE SECOND SEMESTER ENGLISH DEPARTMENT STUDENTS OF CULTURES SCIENCES FACULTY OF SEBELAS MARET UNIVERSITY IN THE ACADEMIC YEAR 2014/2015 - LODYA SESRIYANI (Faculty of training and education, Pamulang university, 2017)
This research dealt with analysis research. It aims to find out: (1) the errors in using cohesive devices in Essay writing written by students; (2) reasons of their errors; (3) the remedial teaching planned to solve the students’ error. This descriptive exploratory study was conducted at the Second Semester of English Department Students of Cultural Sciences Faculty of Sebelas Maret University in the Academic Year 2014/2015. There were 48 students as the sample of this study. They are totally chosen as sample because there are two classes of second semester. The data were collected through observation, document analysis, questionnaire, and interview. The researcher used descriptive analysis as follows: (1) the researcher classified the error after the collecting the data; (2) the researcher identified the type of cohesive devices errors of all students’ essay; (3) the researcher found the causes of errors. There are some research findings: (1) The students make errors in using reference and conjunction; (2) The cause of their error is intralingua error; (3) The remedial teaching is needed by the students. In this case, the researcher suggests to use project based learning. The result of this study implies that the Second Semester English Department Students of Cultures Sciences Faculty of Sebelas Maret University in the Academic Year 2014 /2015 have weaknesses in cohesive devices especially in reference cohesion, the most dominant error is misformation. However, the most dominant error in conjunction is misordering. At last, the teacher needs to apply remedial teaching to solve the students’ error in using cohesive devices, the teacher should use the appropriate activities in writing class. Keywords: cohesive devices, error, intralingua, remedial teaching.